Guidebook on the basic nutrition education for health workers and extension workers in Bangladesh - Nahar, Kamrun; Ali, Hazrat; Khondker, Murshed-E-Jahan; Biswas, Ashutosh; Jaman, Ahmed; Rashid, Harun (WorldFish, 2023)
This training guidebook is a valuable resource for the community health workers and extension workers, offering comprehensive insights into the fundamental principles of nutrition. This guidebook covers different essential topics which emphasize the importance of a balanced diet, discussing the causes, consequences, and prevention of malnutrition. The book provides insights into infant and child nutrition, underlining the significance of proper nourishment during early development. It also addresses the unique needs of pregnant and lactating women, with a special focus on the role of fish in enhancing nutrition for women and children. The guidebook stresses essential practices like handwashing, food safety, and the importance of safe water and sanitary toilets. It extends its reach to adolescent nutrition, preventing child marriage, and advocates for family planning services to improve overall nutrition. The guidebook underscores the crucial aspect of gender equality in ensuring comprehensive and fair nutrition for everyone. Overall, its significance lies in its potential to enhance the capacity of frontline workers, ultimately contributing to improved health outcomes and the overall well-being of the communities they serve.